PEMBERDAYAAN PENGELOLAAN SAMPAH BERBASIS KELUARGA MANDIRI DALAM MENJAGA KEBERSIHAN PEKARANGAN RUMAH MENUJU LINGKUNGAN SEHAT DAN EKONOMIS - Riko Irwanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2023)
Garbage is a place for disease agents to develop, whether in the form of bacteria, mosquitoes, cockroaches and rats. These agents carry disease agents that can cause diarrhea, malaria, dengue fever, typhoid and others. The amount of waste in the environment is also related to the increasing population. The environment in the Bangka Belitung Islands Province is also inseparable from the problem of waste management. Especially at the service location, namely in Permis Village, Simpang Rimba District, South Bangka Regency. Permis village is a village with quite a large population in South Bangka district, so waste management and health education are very important. Pemis Village has a population of 3,894 people or a population density of 173.77 people/km2. Permis Village has geographical potential, namely the Permisan Hill and the beach. Permisan Hill or better known as the Mount Permisan Natural Tourism Park (TWA) in Simpang Rimba District, South Bangka Regency which is still natural and has not been managed properly. So it really needs to be managed, especially in an effort to make the area an ecotourism area that can grow people's economic resources. The service program that will be carried out is in the form of Independent Family-Based Waste Management activities within the Permis village population. The activity is in the form of Socialization of an independent family-based waste management system and Involving the Permis village community in the waste management application. The purpose of implementing this service is to build community commitment and awareness about the importance of good waste management towards a healthy and economically valuable family environment. So that it is hoped that an independent, healthy and competitive society will be formed.